Private Deeds In Civil Evidence Practice: Analysis Of Formal And Material Validity - Diana Pujiningsih; Rizki Wahyudi; Yulia Rachmawati; Johannes Triestanto; Rafiqi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Private deeds constitute one of the written evidentiary instruments frequently utilized in Indonesian civil litigation, particularly in disputes arising from contractual relationships and private legal engagements. This study aims to examine the legal standing of private deeds within the civil evidentiary system by emphasizing both formal validity and substantive validity, as well as their implications in judicial proof. The analysis focuses on the normative regulation of private deeds under the Indonesian Civil Code, doctrines of civil evidence law, and scholarly perspectives developed in national legal journals. This research employs a normative juridical method using statutory and conceptual approaches. Data were collected through library research, encompassing legislation, legal textbooks, and relevant academic journal articles addressing private deeds and their evidentiary force. The data were analyzed qualitatively to assess the coherence between positive legal norms and their application in judicial practice. The findings indicate that private deeds possess a relative evidentiary value, which depends on the fulfillment of formal requirements, namely written form and the signatures of the parties, as well as substantive requirements relating to the authenticity and legality of the content. When both the signature and the substance of the deed are acknowledged by the interested parties, a private deed may function as strong evidence before the court. Conversely, when denial or dispute arises, such a deed requires corroboration by other forms of evidence to strengthen its probative value. Accordingly, formal and substantive validity play a decisive role in determining the effectiveness of private deeds in civil evidentiary proceedings.